2003
DOI: 10.1161/01.hyp.0000053552.86367.12
|View full text |Cite|
|
Sign up to set email alerts
|

Enhancement of Ischemia-Induced Angiogenesis by eNOS Overexpression

Abstract: Abstract-It remains undetermined whether continuous endothelial nitric oxide (NO) overexpression exerts angiogenic action. We surgically induced hindlimb ischemia in transgenic mice overexpressing endothelial NO synthase in the endothelium (eNOS-Tg) and studied neocapillary formation, ischemia-induced vascular endothelial growth factor (VEGF) expression, cGMP accumulation, and Akt/PKB signaling. Laser Doppler imaging revealed a markedly increased recovery of blood perfusion in ischemic limbs of eNOS-Tg mice (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
72
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 41 publications
2
72
0
2
Order By: Relevance
“…12 We believe that eNOS up-regulation induced by repeated thermal therapy is caused by an increase in cardiac output and blood flow, which in turn results in increased shear stress, although thermal stimulation might up-regulate arterial eNOS directly. 13,17 Repeated thermal therapy increases cardiac output, shear stresses of the vessel wall and ultimately eNOS expression.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…12 We believe that eNOS up-regulation induced by repeated thermal therapy is caused by an increase in cardiac output and blood flow, which in turn results in increased shear stress, although thermal stimulation might up-regulate arterial eNOS directly. 13,17 Repeated thermal therapy increases cardiac output, shear stresses of the vessel wall and ultimately eNOS expression.…”
Section: Discussionmentioning
confidence: 97%
“…11 Amano et al demonstrated that transgenic mice overexpressing eNOS in the endothelium increased new capillary formation in response to tissue ischemia. 12 Namba et al reported that intramuscular injection of bovine eNOS plasmid induced therapeutic angiogenesis in a rat ischemic hindlimb model. 19 Thus, NO is a critical regulatory molecule for angiogenesis in response to tissue ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…In eNOS-deficient mice neovascularization is decreased, resulting in severe limb loss 14 ; in parallel, up-regulation of eNOS activity by eNOS gene delivery 15 or bovine eNOS overexpression 16 enhances postischemic blood flow recovery and limb function. In our study we confirmed these findings in healthy mice and extended them to a more clinically relevant model, the diabetic and atherosclerotic mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of neovascularization induced by NO might be due to induction of VEGF, although enhancement of ischemia-induced angiogenesis by eNOS overexpression was reported not to be dependent on VEGF in transgenic mice. 35 Continuous expression of NO might work, as angiogenic factors use other pathways. In addition, stimulation of new vessel formation by eNOS is likely to create new therapeutic options in angiogenesisdependent conditions such as wound healing, ischemic Figure 5.…”
Section: Discussionmentioning
confidence: 99%